Protocolos de segurança do paciente: proposta de um recurso educacional informatizado - Camargo, André Bueno de (Universidade Federal de São Carlos, 2013)
This study aimed to develop a computerized educational resource on Patient Safety, and propose a Choosing Priorities in Education Service Tool, which give rise to a questionnaire rank the educational actions which should be priority. The creation of this resource was marked in Planning Learning Activities Supported by Computers, which is a methodology for developing educational content supported by computer. Evaluated the technical quality and usability of the resource based on the scale SUS (System Usability Scale), which quickly evaluates the usability of systems. The feature that prioritizes the educational measures was evaluated positively, can turn into a powerful educational tool in nursing education.
Keywords: Enfermagem; Educação permanente; Informática na educação; Instrução por computador; Segurança do paciente; Tecnologia educacional; Computer-assisted instruction; Patient safety; Educational technology; Education; Nursing; CIENCIAS DA SAUDE::ENFERMAGEM